Implementasi Manajemen dan Digitalisasi Perpustakaan di SMAN 1 Kedamean - Naziyatun, Syifa; Kharisma, Aisca Nindy; Maritza, Khansa Indiko Aulia; Hanifah, Nur Komala; Salsabila, Farah Fredlina; Salsabila, Violinda Fitri; Risky, Bella Adinda; Fitria, Rezki Nurma (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
The swift advancement of information technology has led to major changes in the education field, especially concerning school library services. This research investigates the management and digitalization of the library at SMAN 1 Kedamean as a strategic move to improve the quality and availability of information services for both students and teachers. The study utilizes a qualitative descriptive approach, featuring observation and documentation, to evaluate the library’s organizational structure, classification, and cataloging methods. Findings reveal that the adoption of a digital library management system employing the Dewey Decimal Classification and digital cataloging tools has enhanced the efficiency of book management, lending processes, and information retrieval. The digital library also provides online access to its catalog, promoting self-guided learning and encouraging digital literacy among students. Additionally, the library's transformation is supported by training initiatives focused on scientific writing and the use of digital tools, establishing the library as a center for active learning and innovation. In summary, the digitalization and organized management of the SMAN 1 Kedamean library have bolstered its capacity to support academic endeavors and cultivate a research-oriented academic culture.